Description of Physical Fatigue Among Brickmakers in Pangkah Village - Nooryana, Syavira; Khofifah; Amanah, Septi (FISIO MU: Physiotherapy Evidences, 2026)
Introduction: Fatigue is a protective mechanism that the body activates to prevent further damage, and recovery can occur after adequate rest. Occupational fatigue is often characterised by decreased energy in performing daily tasks or activities, which can lead to increased errors and, in more serious cases, accidents. The effects of fatigue can reduce work capacity and endurance, as seen in the sensation of tiredness, slowed reactions, difficulty in decision-making, and decreased motivation. When fatigue levels are high, this can hinder worker productivity. This study aims to determine the picture of physical fatigue in brick makers in Pangkah village. Methods: This study uses a quantitative descriptive research design to provide an overview of the physical job fatigue experienced by brick-making workers in Pangkah village. Determination of the sample using purposive sampling technique, the number of samples is 59 people who are brick making workers in Pangkah village. Physical work fatigue in brick-making workers is measured using the Subjective Self Rating Test (SSRT) questionnaire. Results: Based on the research that has been done, the results of measurements using the Subjective Self Rating Test (SSRT) questionnaire show that workers experience work fatigue in the low category, namely 64.4%, moderate fatigue as much as 33.9%, and high fatigue of 1.7%. Conclusion: All brick makers in Pangkah village experience work fatigue caused by several factors, both internal and external, which interfere with their work activities.